UNC93B1 interacts with the calcium sensor STIM1 for efficient antigen cross-presentation in dendritic cells. Issue 1 (December 2017) - Maschalidi, Sophia; Nunes-Hasler, Paula; Nascimento, Clarissa; Sallent, Ignacio; Lannoy, Valérie; Garfa-Traore, Meriem; Cagnard, Nicolas; Sepulveda, Fernando; Vargas, Pablo; Lennon-Duménil, Ana-Maria; Endert, Peter; Capiod, Thierry; et al.
Abstract Dendritic cells (DC) have the unique ability to present exogenous antigens via the major histocompatibility complex class I pathway to stimulate naive CD8+ T cells. In DCs with a non-functional mutation inUnc93b1 (3d mutation), endosomal acidification, phagosomal maturation, antigen degradation, antigen export to the cytosol and the function of the store-operated-Ca2+ -entry regulator STIM1 are impaired. These defects result in compromised antigen cross-presentation and anti-tumor responses in 3d-mutated mice. Here, we show that UNC93B1 interacts with the calcium sensor STIM1 in the endoplasmic reticulum, a critical step for STIM1 oligomerization and activation. Expression of a constitutively active STIM1 mutant, which no longer binds UNC93B1, restores antigen degradation and cross-presentation in 3d-mutated DCs. Furthermore, ablation of STIM1 in mouse and human cells leads to a decrease in cross-presentation. Our data indicate that the UNC93B1 and STIM1 cooperation is important for calcium flux and antigen cross-presentation in DCs. STIM proteins sense Ca2+ depletion in the ER and activate store-operated Ca2+ entry in response, a process associated with dendritic cell (DC) functions. Here, the authors show that optimal antigen cross-presentation in DCs requires the association of the chaperone molecule UNC93B1 with STIM1.